Finite Element Modelling of Exotic Options - Jürgen Topper (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 1998)
The Finite Element Method is a well-studied and well-understood method of solving partial differential equations. It's applicability to financial models formulated as PDEs is demonstrated. It's advantage concerning the computation of accurate `Greeks' is delineated. This is demonstrated with various exotic options.
Keywords: C63; G13; 330